2007
DOI: 10.1111/j.1545-5300.2007.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Resilience: Families and Communities as Agents for Change

Abstract: In this article, the Linking Human Systems (LINC) Community Resilience model, a theoretical framework for initiating and sustaining change in communities that have undergone rapid and untimely transition or loss, is presented. The model assumes that individuals, families, and communities are inherently competent and resilient, and that with appropriate support and encouragement, they can access individual and collective strengths that will allow them to transcend their loss. This competence can be nurtured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 28 publications
3
90
0
11
Order By: Relevance
“…Berger (2005) concluded that adopting a multi-systemic approach was effective, not only in dealing with individuals and families, but also in changing the mood and functioning of the community. Ager et al (2010), Kumpfer and Summerhays (2006), Landau (2007), Mertensmeyer and Fine (2000 and Ungar (2010) cite similar theoretical frameworks for assessing, initiating and sustaining change in traumatised individuals and families.At a different level, Stewart et al (2009) discuss the interrelationships between public and private organisations to support community resilience and described a model of interaction that parallels Bronfenbrenner's framework. Community resilience is embedded within its economic and social systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Berger (2005) concluded that adopting a multi-systemic approach was effective, not only in dealing with individuals and families, but also in changing the mood and functioning of the community. Ager et al (2010), Kumpfer and Summerhays (2006), Landau (2007), Mertensmeyer and Fine (2000 and Ungar (2010) cite similar theoretical frameworks for assessing, initiating and sustaining change in traumatised individuals and families.At a different level, Stewart et al (2009) discuss the interrelationships between public and private organisations to support community resilience and described a model of interaction that parallels Bronfenbrenner's framework. Community resilience is embedded within its economic and social systems.…”
mentioning
confidence: 99%
“…Berger (2005) concluded that adopting a multi-systemic approach was effective, not only in dealing with individuals and families, but also in changing the mood and functioning of the community. Ager et al (2010), Kumpfer and Summerhays (2006), Landau (2007), Mertensmeyer and Fine (2000) and Ungar (2010) cite similar theoretical frameworks for assessing, initiating and sustaining change in traumatised individuals and families.…”
mentioning
confidence: 99%
“…Sin embargo, se requiere mucha más investigación desarrollada específicamente desde este enfoque, lo que implica ciertos desafíos metodológicos que se analizarán en la discusión. aplicaciones posibles del enfoque de resiliencia familiar el concepto de resiliencia familiar ha sido aplicado recientemente en la terapia familiar (Hawley, 2000;Walsh, 2003), en los programas integrales de intervención clínica familiar (lee, greene, Hsu, Solovey, grove, Fraser et al, 2009), en intervención psicosocial con familias multiproblemáticas (Sousa, 2008), en servicios de terapia ocupacional y salud mental (abelenda & Helfrich, 2003), en el campo de la salud familiar (borges & Silva, 2010) y en el manejo de catástrofes naturales, terrorismo o crisis económicas (landau, 2007, 2010Walsh, 2007). a continuación se muestran iniciativas implementadas en Chile que se consideran potencialmente congruentes con los principios de un modelo ecosistémico de resiliencia familiar, en tres áreas de alta relevancia pública: la promoción del desarrollo infantil temprano; la prevención secundaria del maltrato infantil y la negligencia parental; y la atención en centros de salud familiar.…”
Section: Familias a Lo Largo Del Ciclo Vitalunclassified
“…esto muestra que podemos estimular la resiliencia familiar desde nuestro rol profesional, ya sea: disminuyendo las demandas y tensiones que sobrepasan a la familia, facilitando su capacidad de contrapeso; promoviendo y movilizando sus capacidades, fortalezas y recursos disponibles -en ellas mismas y en su entorno-; estimulando la cohesión o conexión relacional entre sus miembros; y elaborando y modificando sus sistemas de creencias y significados compartidos (Hawley, 2000;Kalil, 2003;landau, 2007, 2010Patterson, 2002b;Sousa, 2008;Walsh, 2003Walsh, , 2007. es importante, en el análisis previo a comenzar la intervención, darse tiempo para identificar claramente el escenario que se enfrenta (riesgo, deterioro o tensión familiar) para seleccionar la estrategia adecuada a seguir (contrapeso, recuperación o fortalecimiento preventivo).…”
Section: Familias Con Un Hijo Autistaunclassified
See 1 more Smart Citation